Norquandrangularic acid D, a new trinorcycloartane isolated from the leaves of Combretum quadrangulare. Issue 7 (3rd July 2022) - Nguyen, Huu-Hung; Bui, Xuan-Hao; Tran, Thi-Minh-Dinh; Sichaem, Jirapast; Le, Thi-Kim-Dung; Nguyen, Ngoc-Hong; Duong, Thuc-Huy
Abstract: Phytochemical investigation on the leaves of Combretum quadrangulare growing in Vietnam afforded a new trinorcycloartane triterpenoid, norquandrangularic acid D (1 ), along with three known compounds, betulinic acid (2 ), luteolin (3 ), and apigenin (4 ). Their structures were elucidated using spectroscopic methods and comparison was made with reports in the literature. Compounds 1 and 3 were evaluated for α -glucosidase inhibition. Compound 3 showed significant activity, with an IC50 value of 11.39 µM, (acarbose, used as a positive control, had an IC50 of 367 µM). Abstract : UF0001